Digital Switching System / Kamarunizam Hashim and Wan Mohd. Faizul Ismail - Hashim, Kamarunizam; Ismail, Wan Mohd. Faizul (2000)
The main features of this project are actually based on the needs of some peoples push-to-on switches to control any one out of 16 device. Digital Switching System used simple electronic devices such as integrated circuit, relay, transistor, resistor and etc. the function of the circuit will be explained detail in this project. This circuit needs to connect to load, which can be any electric devices such as lamp, radio, rice cooker and etc. The circuit comprises three switches that are used to switch on the electrical equipment in up, down sequence and reset mode. nowadays to figure out obstacles in daily life. This project offers the use of only three